Characteristics and outcomes among vaccinated lung transplant patients with breakthrough COVID‐19. Issue 2 (19th January 2022) - Bollineni, Srinivas; Mahan, Luke D.; Duncan, Patrick; Mohanka, Manish R.; Lawrence, Adrian; Joerns, John; Timofte, Irina; Torres, Fernando; La Hoz, Ricardo M.; Kershaw, Corey D.; Terada, Lance S.; Kaza, Vaidehi; et al.
Abstract: Background: Despite multiple studies evaluating the immunological responsiveness to vaccines, the clinical effectiveness of the two‐dose mRNA vaccine schedule among lung transplant (LT) patients has not been evaluated. Methods: We included LT patients who tested positive for SARS‐CoV‐2 on a nasopharyngeal swab between March 1, 2020, and August 25, 2021 ( n  = 70). The study group was divided based on their vaccination status. Results: During the study period, 14 fully vaccinated LT patients with one of the mRNA vaccines tested positive for COVID‐19 (median age 54, range 30–62 years, M:F 9:5). The vaccinated cohort was younger with bilateral LT, have suppurative conditions as the transplant indication, and present with milder symptoms. However, pulmonary parenchymal involvement was seen among all 12 patients where computed tomography (CT) of chest was available. The laboratory profile indicated a more subdued inflammatory response among the vaccinated group. A lower proportion of vaccinated patients developed respiratory failure, needed ICU admission or ventilator support, although none of the differences achieved statistical significance. None of the vaccinated patients succumbed to COVID‐19 during the study period, while the 4‐week mortality among unvaccinated patients was nearly 15% (8/56). Conclusions: In this cohort of vaccinated LT patients who developed breakthrough COVID‐19, the clinical course, risk of complications, and outcomes trended better than unvaccinated patients. However, universal involvement of the allograft demonstrates the continued vulnerability of these patients to significant sequelae from COVID‐19. Future studies may evaluate the incremental protection of vaccination after the completion of the third dose of mRNA vaccines among LT patients.